Underwriter Reputation and Underpricing: Navigating the Moderating Effects of Company Size - Jamian Purba; Maulina Permatasari; Benny Oktaviano (LPPM Universitas Pelita Bangsa, 2025)
This study investigates the influence of underwriter reputation and company size on IPO underpricing, as well as the moderating effect of company size on the relationship between underwriter reputation and IPO underpricing. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the analysis was conducted on IPO data from 2020-2024. The results reveal that underwriter reputation has a significant negative effect on IPO underpricing, indicating that reputable underwriters can reduce initial return volatility. However, company size does not have a significant direct impact on IPO underpricing. Furthermore, the moderating analysis shows that company size significantly strengthens the negative relationship between underwriter reputation and IPO underpricing, suggesting that larger firms with reputable underwriters tend to experience more stable IPO pricing. These findings contribute to the literature by highlighting the combined role of firm size and underwriter credibility in mitigating IPO underpricing, providing implications for issuers, investors, and policymakers in emerging markets. Keywords: Underwriter Reputation, Company Size, IPO Underpricing, Moderation Effect, PLS-SEM